Civic Participation in Climate Change Policy Implementation in Ho Chi Minh City - Son, Ngo Hoai; Hoa, Nguyen Van (VNU Journal of Science: Policy and Management Studies, 2020)
With questionnaires from 210 respondents, the author came to conclusion that civic participation in climate change policy implementation in Ho Chi Minh City was not effective. All eight forms of participation were rated below 30%; no form of participation was effective. The reason behind this fell in the lack of regulation framework for civic participation. Then an appropriate solution is to establish such regulation framework for mobilising civic participation. In addition, Ho Chi Minh City government should set up a civic participation framework to organise effectivecivc participation as well as monitor this activity.